MODEL OF ACOUSTIC EMISSION SIGNALS IN FRICTION SURFACE BASED ON COMPOSITE MATERIALS - Філоненко, С.; Косицька, Т.; Космач, О. (Science-based technologies, 2010)
The model of the resulting AE signal, which is formed at the stage of normal wear of the friction surfaces based on composite material, is conducted. The modeling of resulting AE signal at the constant axial load and change of the friction pair speed, variations start time destruction of elements in contact interaction platform at given speed and variation of damaged elements number at given speed are showed.